Vectors for expression and modification of cDNA sequences in Neurospora crassa. - J. W. Campbell; C. S. Enderlin; C. P. Selitrennikoff (Fungal Genetics Reports, 1994)
The quinic acid inducible qa-2 promoter of Neurospora crassa has been used to express cloned genes by a number of different groups. However, most of the commonly available sources of this promoter require extensive sub-cloning and modification before they can be used as effective expression vectors. We report the construction of two plasmids that allow direct cloning and subsequent expression in N. crassa. Each plasmid also has a number of useful features to aid in detecting and modifying insert sequences.